DYNAMIC FOLLOW UP OF APHASIC DISORDERS IN PATIENTS WITH ISCHEMIC STROKE IN ACUTE STAGE - Dora Peychinska; Maya Danovska; Dimitar Chakarov; Virginia Simeonova; Christo Lilovski (Peytchinski Publishing, 2004)
The dynamic follow up of aphasic disorders in patients with acute ischemic stroke is of great importance because of its prognostic value for their future recovery. The purpose of that clinical study is to compare the type of aphasia with the CT data about the infarction localization and to evaluate the prospective aphasia recovery. In the clinical study were included 37 patients with ischemic stroke and aphasia, theated in II-nd Neurology Clinic, Medical University Pleven. The diagnosis ischemic stroke was confirmed by clinical and CT investigations. Partial and full recovery of sensory aphasia was registered in all the patients with total aphasia, while motor aphasia showed little tendency of reduction in acute ischemic stroke. Aphasic disorders were more severe in cases with ischemic infarctions localized in the specific anatomical regions responsible for the speech function. The dynamic follow up of aphasic disorders has prognostic value for the speech recovery. Better prognosis show sensory and amnestic aphasia. Lesion localization also influences the prognosis.